The Effect of APBN Spending on Work Units (Satker) KPPN Tanjung Redeb on Economic Growth in Berau Regency, East Kalimatan - Sulistyo, Indra (Oikonomia: Jurnal Manajemen, 2024)
Purpose The purpose of this research is to determine the effect of APBN allocation through personnel expenditure, goods expenditure and capital expenditure on the economic growth of Berau Regency, East Kalimantan. Methodology The research method used is quantitative research using an associative approach with secondary data sourced from all ministries and government institutions under the work unit area managed by the Tanjung Redeb KPPN, Berau Regency, a total of 27 work units spanning the period 2010-2021. The analytical tool used is panel data regression analysis. Findings The results of this study show that personnel spending and goods spending have a significant positive effect on economic growth. Meanwhile, capital expenditure does not show a significant influence on economic growth. Suggestion This has the implication that the APBN allocation through the allocation of types of government spending, especially personnel spending and goods spending in Berau Regency, is focused on efforts to increase the production of goods and services in the regional economy and also on productive economic activities so as to have an effect on local regional economic growth. This is different from capital expenditure which tends to show long-term effects..